Geometry of bifurcation sets of generic unfoldings of corank two functions - Saji, Kentaro; dos Santos, Samuel Paulino [UNESP] (Springer Nature, 2021)
We study the geometry of bifurcation sets of generic unfoldings of D4±-functions. Taking blow-ups, we show each of the bifurcation sets of D4±-functions admits a parametrization as a surface in R3. Using this parametrization, we investigate the behavior of the Gaussian curvature and the principal curvatures. Furthermore, we investigate the number of ridge curves and subparabolic curves near their singular point.
Keywords: Bifurcation set; Caustics; Parabolic curve; Principal curvature